GAMBARAN KEINGINAN KELOMPOK LELAKI SEKS LELAKI DALAM MEMANFAATKAN KLINIK VOLUNTARY COUNSELLING AND TESTING DI PUSKESMAS CIPUTAT - Kamila Rahmadiah; Fajar Ariyanti (Jurnal Kesehatan Reproduksi, 2020)
Abstract Background: Men Who Have Sex with Men (MSM) is a high-risk group of people getting infected with HIV/AIDS due to their multiple sexual partner behaviour and their anal intercourse practices. The MSM group is the highest risk factor for HIV new cases in Indonesia. The VCT (Voluntary Counselling and Testing) clinic is the main entrance to HIV/AIDS prevention, maintenance, support, and treatment services. However, the MSM group that utilizes VCT clinic in Ciputat subdistrict decreased from the previous year. Objective: The purpose of this research was to thorouglhly identify about the overview of the intention of men who have sex with men groups in utilizing voluntary counselling and testing clinic in Ciputat public health center. Method: This research was a descriptive qualitative research using the case study method, which was conducted in February-November 2019 in the working area of ​​the Ciputat public health center. The main informants were homosexual or bisexual groups, who were selected by purposive sampling. Data validation used source triangulation, and data were analyzed by content analysis. Result: The results showed that most of the informant had no intention to utilize the VCT clinic in Ciputat public health center, low knowledge of HIV/AIDS and VCT clinic, low susceptibility of perception and self-efficacy. All informants had barriers, high perception of severity, perception of good benefit, and quite large cues to act. Conclusion: The majority of informants had no intention to utilize the VCT clinic due to low knowledge of HIV/AIDS and VCT clinic. Public health center and NGOs are recommended to collaborate in increasing knowledge of community on HIV/AIDS and VCT clinic. Keywords: men who have sex with men, VCT clinic, HIV/AIDS Abstrak Latar belakang: Lelaki Seks Lelaki (LSL) merupakan kelompok berisiko tinggi tertular HIV/AIDS dikarenakan kecenderungannya berganti pasangan dan melakukan seks anal. Kelompok LSL merupakan faktor risiko tertinggi kasus baru HIV di Indonesia. Klinik VCT (Voluntary Counselling and Testing) merupakan pintu masuk utama pada layanan pencegahan, perawatan, dukungan, dan pengobatan HIV/AIDS. Namun LSL yang memanfaatkan klinik VCT di Kecamatan Ciputat mengalami penurunan dari tahun sebelumnya. Tujuan: Tujuan penelitian ini adalah untuk mengetahui secara mendalam mengenai gambaran keinginan kelompok LSL dalam memanfaatkan klinik VCT di Puskesmas Ciputat. Metode: Penelitian ini merupakan penelitian kualititatif deskriptif dengan metode studi kasus, yang dilaksanakan pada Februari-November 2019 di wilayah kerja Puskesmas Ciputat. Informan utama adalah kelompok homoseksual maupun biseksual yang dipilih dengan cara purposive sampling. Validasi data menggunakan triangulasi sumber dan analisa data dilakukan dengan content analysis. Hasil: Hasil penelitian menunjukkan sebagian besar informan belum memiliki keinginan untuk memanfaatkan klinik VCT di Puskesmas Ciputat, berpengetahuan kurang mengenai HIV/AIDS maupun klinik VCT, serta memiliki persepsi kerentanan dan efikasi diri yang rendah. Semua informan memiliki hambatan, persepsi keparahan yang tinggi, persepsi manfaat yang baik, serta isyarat untuk bertindak cukup besar. Kesimpulan: Sebagian besar LSL belum memiliki keinginan untuk memanfaatkan klinik VCT. Hal ini karena informan memiliki pengetahuan yang kurang terkait HIV/AIDS maupun klinik VCT. Puskesmas dan LSM diharapkan dapat bekerja sama untuk dapat meningkatkan pengetahuan masyarakat mengenai HIV/AIDS dan klinik VCT. Kata kunci: lelaki seks lelaki, klinik VCT, HIV/AIDS